Navigating the Promise and Perils: Artificial Intelligence in Assisted Reproductive Techniques - Pradhan, Tarun (Birat Journal of Health Sciences, 2024)
The inclusion of artificial intelligence (AI) into assisted reproductive techniques (ART) represents a significant advancement in the field of reproductive medicine. AI shows the confidence of enhancing various aspects of ART, including treatment optimization, embryo selection, and predictive modeling. However, as with any emerging technology, the adoption of AI in ART necessitates careful consideration of ethical, legal, and social implications. This editorial aims to explore the dual role of AI in ART as a potential game-changer while emphasizing the need for caution and ethical blunder.